The Influence of Perceived Usability on Learning Management System Acceptance of Lecturers in Ghana: A PLS-SEM Disjoint Two-Stage Approach - Adolph Sedem Yaw Adu; Judy Van Biljon; Ronell van der Merwe (Advances in Human-Computer Interaction)
This paper reports on the investigation of low learning management system (LMS) adoption by Ghanaian lecturers and proposes a statistical model to understand and predict the influence of perceived usability (PUsab) on lecturers’ LMS usage. A total of 255 lecturers from four higher education institutions (HEIs) in Ghana responded to the survey during the 2023/2024 academic year. Partial least squares structural equation modeling (PLS-SEM) was applied to test the proposed research model. The PLS-SEM results confirmed that human factors, organizational support, and social influence have a statistically significant impact on the PUsab of LMSs, and specifically, PUsab was found to have significantly influenced LMS use among lecturers. In addition to proposing the inclusion of the usability construct in modeling LMS adoption, the paper makes a knowledge contribution by mapping factors from the technology acceptance literature (attitude acceptance) to those from the usability literature (behavior acceptance) toward understanding LMS adoption. The practical contribution of this study is twofold: first, to inform designers and guide HEI managers in considering the contextual factors during the prepurchase evaluation of LMSs; and second, to provide a validated questionnaire which can be employed in similar studies as a reliable tool for assessing LMS adoption.